Efektivitas Pendidikan Kesehatan Metode Buzz Group terhadap Peningkatan Pengetahuan Masyarakat Tentang Demam Berdarah - Sri Agustina; Herlina Herlina; Yunisman Roni (Jurnal Ventilator, 2025)
Background: Dengue fever is an endemic diseases caused by the dengue virus which is transmitted by the Aedes aegypti mosquito. Knowledge have a crucial role in preventing and controlling dengue fever. The purpose of this study is to examine the effectiveness of health education using the buzz group discussion method in increasing community understanding of dengue Methods: Quantitative research with quasi experimental design pre-test and post-test with Non-equivalent control group pretest-posttest. This study was conducted in Sidomulyo Timur with a total sample of 32 respondents chosen based on inclusion criteria using purposive sampling technique. Data analysis used is Wilcoxon test and Man-Whitney test. Results: There was an increase knowledge in the experimental group by 26.56%, with a good level of knowledge of 81.3% after being given health education by the buzz group method. Statistical tests obtained the results of the p value (0.000) < ? (0.05). Which means there is an increase in knowledge after the intervention. Conclusion: Health education using the buzz group method about dengue fever is effective in increasing community knowledge.